2016
DOI: 10.1002/2016ja022489
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar features of the low‐latitude and midlatitude ionospheric response to the St. Patrick's Day geomagnetic storm of 17 March 2015

Abstract: The current study aims at investigating and identifying the ionospheric effects of the geomagnetic storm that occurred during 17–19 March 2015. Incidentally, with SYM‐H hitting a minimum of −232 nT, this was the strongest storm of the current solar cycle 24. The study investigates how the storm has affected the equatorial, low‐latitude, and midlatitude ionosphere in the American and the European sectors using available ground‐based ionosonde and GPS TEC (total electron content) data. The possible effects of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 67 publications
9
65
0
Order By: Relevance
“…As, the ionosphere itself is uplifted well above the path of the satellite, it measures such a small density which seems much smaller than the quiet time values. This particular SWARM observation (figure 2g) was also discussed in recent studies by Ram et al (2015) and Nayak et al (2016). Ram et al (2015) also suggested the presence of a strong eastward prompt penetration electric field in the Indian longitudes which was superposed on the pre reversal enhancement (PRE) electric field to lift the equatorial plasma to higher altitudes and the corresponding enhancement of the EIA.…”
Section: Equatorialmentioning
confidence: 63%
See 1 more Smart Citation
“…As, the ionosphere itself is uplifted well above the path of the satellite, it measures such a small density which seems much smaller than the quiet time values. This particular SWARM observation (figure 2g) was also discussed in recent studies by Ram et al (2015) and Nayak et al (2016). Ram et al (2015) also suggested the presence of a strong eastward prompt penetration electric field in the Indian longitudes which was superposed on the pre reversal enhancement (PRE) electric field to lift the equatorial plasma to higher altitudes and the corresponding enhancement of the EIA.…”
Section: Equatorialmentioning
confidence: 63%
“…As a result, it has garnered considerable interest in the scientific community. There have been a number of studies which investigated the ionospheric effects of this particular storm (Astafyeva et al, 2015;Cherniak et al, 2015;Kakad et al, 2016;Ramsingh et al, 2015;Nayak et al, 2016;Joshi et al, 2016;Nava et al, 2016;Ram et al, 2015). The study by Carter et al (2016) has studied the global variation of plasma bubble occurrence during the St. Patrick's Day storm.…”
Section: Introductionmentioning
confidence: 97%
“…The green vertical short lines at the bottom of each plot mean that the ionogram is recorded but the trace is too poor to validate a reliable value of f o F 2 . Also, Nayak et al [2016] reported such hemispherical asymmetry but in the American and European sectors, suggesting that such asymmetry is a nonlocal effect related to the neutral wind circulation and to the equinoctial conditions [Fuller-Rowell et al, 1996;Goncharenko et al, 2007]. By comparing the response to the storm depicted by the two ionosondes, we remind the reader that the two ionosondes are is significantly smaller than the lower boundary limit defined by the mean minus the standard deviation.…”
Section: Magnetic Data 221 Ground-based Magnetometersmentioning
confidence: 82%
“…The March 2015 storm, triggered by CMEs, was the strongest storm in solar cycle 24 so far, and some studies on the ionosphere response of this storm have been made [e.g., Cherniak et al, 2015;Astafyeva et al, 2015;Liu et al, 2016aLiu et al, , 2016bZhong et al, 2016;Nayak et al, 2016]. Liu et al [2016a] studied the ionospheric stormenhanced density (SED) in the main phase and found that there was a SED in TEC but not in N m F 2 .…”
Section: Introductionmentioning
confidence: 99%